The influence of hyperplasticizer on concrete - Gordana Broćeta; Mijović Danijela Đurić; Milka Škrbić (Zaštita Materijala)
The paper presents the possibility of modeling of concrete properties in fresh and/or hardened state by applying hyperplasticizers type admixtures, based on a modified polycarboxyl ether polymer. It provides an overview of its application in their own and other experimental surveys with the experiences of the amount and mode of administration, mechanism of action, combination with other admixtures and the impact on other component materials. The test results demonstrate the possibility of achieving a high level of flowability of fresh concrete (absence of bleeding and/or segregation), a modification of the pores in cement matrix, an increase of compressive strength - wich further increases the durability of concrete.